Efektivitas Dwiwatch Vider untuk Meningkatkan Kedisiplinan Waktu di Sekolah bagi Anak Tunarungu - Wahyuni, Dwi; Armaini, Armaini (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This research is motivated by the problem that there are five deaf people, deaf children experience obstacles in their activities, are not independent and still need help from others. This study aims to prove the effectiveness of Dwiwatch Vider to improve the discipline of time for deaf children. This study used an experimental method with pre-experimental design or often called a quasi experiment with one group pretest-posttest design The results of the study showed that Dwiwatch Vider was effective in increasing the discipline of time for deaf children